A Hydroxylated Lupeol‐Based Triterpenoid Ester Isolated from the Scurrula parasitica Parasitic on Nerium indicum. Issue 5 (May 2015) - Liu, Quan‐Yu; Wang, Fei; Zhang, Lei; Xie, Jie‐Ming; Li, Peng; Zhang, Yong‐Hong
Abstract (3β, 7β)‐7‐Hydroxylup‐20(29)‐en‐3‐yl hexadecanoate (1), a new lupeol‐based triterpenoid ester, along with sixteen known compounds, 7β, 15α‐dihydroxylup‐20(29)‐ene‐3β‐O‐palmitate (2), lupeol palmitate (3), lupeol (4), 3‐oxolup‐20(29)‐ene (5), ursolic acid (6), cycloeucalenol (7), stigmasterol (8), β‐sitosterol (9), β‐daucosterol (10), quercetin (11), quercetin 3‐O‐α‐L‐arabinoside (12), quercetin 3‐O‐α‐L‐rhamnoside (13), catechin (14), gitoxigenin 3‐O‐α‐L‐rhamnoside (15), gitoxigenin 3‐O‐α‐D‐glucoside (16), and digitoxigenin 3‐O‐α‐L‐rhamnoside (17), was isolated from the leaves of the Southern China mistletoe, Scurrula parasiticaLinn parasitic on Nerium indicumMill. Their structures were elucidated by spectroscopic analyses, including 2D‐NMR techniques. Cytotoxic activities of compounds 1–7 and 11–17 were evaluated against three cancer cell lines, PANC‐1, HL‐60, and SGC‐7901, revealing that compounds 4, 6, 11, and 15–17 exhibited effective cytotoxicities, while others were inactive. A structureactivity relationship study of compounds 1–5 indicated that the 3‐OH group in lupeol‐based triterpenoids is essential for antitumor activity.